Comparison of the Effects of Sevoflurane and Desflurane on Endothelial Glycocalyx in Patients Undergoing Laparoscopic Hysterectomy: A Randomized, Double-Blind Trial - Kemal Tolga Saraçoğlu; Tahsin Şimşek; Hande Gürbüz; Fatih Doğu Geyik; Ebru Kale; Kürşad Nuri Baydili; Raghad Giuma M. Kordi; Ahmet Kale; Ayten Saraçoğlu (Turkish Journal of Anaesthesiology and Reanimation, 2024)

(untitled)
Objective: Various enzymes, reactive oxygen species, inflammatory conditions, and major surgeries cause endothelial glycocalyx breakdown. Inhalation of anaesthetic agents may have protective effects on the endothelium. This study compared syndecan-1 and heparan sulfate levels to evaluate the effects of sevoflurane and desflurane on the endothelial glycocalyx. Methods: This prospective randomized, double-blind study included 46 patients undergoing laparoscopic hysterectomy. The participants were allocated into sevoflurane and desflurane groups. Subsequently, blood samples were drawn at three time points: before anaesthesia induction for a baseline value (T0), after pneumoperitoneum (T1), and after extubation (T2). Heparan sulfate and syndecan-1 levels were measured. Results: There was no statistical difference between the sevoflurane and desflurane groups in terms of heparan sulfate and syndecan-1 levels at any time point. A significant difference was found only in the desflurane group in the intragroup comparisons of the measurements of heparan sulfate levels (χ2=29.826, P < 0.001). Matched pairs of the time points in the desflurane group showed that P=0.036 (Z=-2.099) for T1-T0, P < 0.001 (Z=-3.924) for T2-T0, and P < 0.001 (Z=-4.197) for T2-T1. The change in percentage between T2 and T1 of heparan sulfate in the desflurane group was found to be statistically significant (P=0.034). Conclusion: The damage caused by surgical stress on the endothelial glycocalyx can be reduced by both desflurane and sevoflurane. The protective effect of desflurane is more prominent than that of sevoflurane.